The Ability on Persuasive Essay Written by the Fourth Semester Students of IKIP-PGRI Pontianak - Ageung Darajat; Muhammad Iqbal Ripo Putra (Edukasi: Jurnal Pendidikan, 2016)
The objectives of this research are to find out (1) the types of errors of a persuasive essay written by the fourth semester students of IKIP-PGRI Pontianak in academic year 2015/2016; (2) the causes of the students’ errors in their writing of persuasive essay. This research is descriptive and carried out in July 2015 at the fourth semester students. The sample of the research is 18 students of class B1, taken by cluster random sampling. To collect the data, the researcher uses an essay test in the form of persuasive essay written by the fourth semester students. Then, the data are analyzed by using error analysis procedure which consists of collecting the data, identifying students’ errors, describing the errors, explaining the errors, and evaluating the errors. The results of the data analysis show that the errors made by the students based on surface strategy taxonomy are classified into omission, addition, misformation, misordering, and combination error. The researcher found 79 total errors consisting of 27 errors of omission, 18 errors of addition, 23 errors of misformation, and 11 errors of combination. Omission error is the most frequent errors made by the students. It is followed by misformation error, addition error, combination error, and misordering error. The factors causing errors made by students are: (1) Interlingual transfer which is caused by the interference of their mother tongue with 28 errors; (2) Intralingual transfer which is caused by the target language itself with 51 errors. The results of this research are beneficial to the process of learning English. The errors which appear in this research can be used as an additional reference to design better teaching material and to improve a technique used in teaching writing. Therefore, the students will not make the same errors.